(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was performed for evaluating the growth and production performances of crossbred climbing perch (Anabas testudineus) during August to October 2009. The crossbred groups of fish were produced by crossing between native climbing perch and Thai climbing perch (A. testudineus). Growth and production performances was compared at grow out condition between crossbred groups in the two reciprocal crosses of treatments viz. T1: Native climbing perch (?) × Thai climbing perch (?) and T2: Thai climbing perch (?)×Native climbing perch (?. At the same time, they were compared also with their respective control F1 pure line groups i.e. T3: Native climbing perch (?) × Native climbing perch (?) and T4: Thai climbing perch (?) × Thai climbing perch (?). It was evident from the results that among the treatments in grow out system, the highest mean harvesting weight was 69.25±9.01 g found in T4 (Thai climbing perch), which was significantly different (P<0.05) from all other treatments. Whereas, T3 (native climbing perch) also showed the lowest mean harvesting weight 33.38±8.74 g and showed significant differences (P<0.05) among all the treatments. The mean harvesting weight of both the crossbred groups i.e. T1 and T2 were 50.83±6.65 and 59.94±7.83 g, respectively and these results were statistically insignificant (P>0.05) between them but significant among all other treatments. The highest (93.60%) and lowest (83.06%) survival rates were observed in Thai koi (T4) and native Koi (T3) parental stocks, respectively. Wider variations in terms of productions performances were observed among the treatments, where the gross production of T1, T2, T3 and T4 were 2,753±96.67, 3,401±73.26, 1,733±168.47 and 4,051±185 kg/ha, respectively. The productions obtained from crossbred groups were at intermediate compared to their control pure line groups. Higher FCR mean value was observed in native control line (T3), while, lower FCR mean value was observed in Thai control line (T4). DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13990 Int. J. Agril. Res. Innov. & Tech. 2 (1): 19-25, June, 2012